2014
DOI: 10.1088/0964-1726/23/11/115006
|View full text |Cite
|
Sign up to set email alerts
|

PACS—Realization of an adaptive concept using pressure actuated cellular structures

Abstract: A biologically inspired concept is investigated which can be utilized to develop energy efficient, lightweight and applicational flexible adaptive structures. Building a real life morphing unit is an ambitious task as the numerous works in the particular field show. Summarizing fundamental demands and barriers regarding shape changing structures, the basic challenges of designing morphing structures are listed. The concept of Pressure Actuated Cellular Structures (PACS) is arranged within the recent morphing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 18 publications
0
40
0
Order By: Relevance
“…For all of these subsystems, conceptual solutions are developed and presented in detail in previous publications [21][22][23][24][25]. The holistic design approach is illustrated in Figure 7.…”
Section: Pacs-concept and Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…For all of these subsystems, conceptual solutions are developed and presented in detail in previous publications [21][22][23][24][25]. The holistic design approach is illustrated in Figure 7.…”
Section: Pacs-concept and Approachmentioning
confidence: 99%
“…Accordingly, FRP prove to be particularly suitable for PACS. In initial trials, the functionality of PACS was demonstrated on a single-row cantilever made of pre-impregnated glass-fiber reinforced plastics (GFRP) [21]. However, the manufacturing process turns out to be complex, time-consuming, and difficult to reproduce.…”
Section: Pacs-concept and Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…A strain energy-based objective function may lead to a better balance of stiffness and flexibility and may also implicitly consider actuator size and system weight in the design. As evident, further development of the continuum gradient-based topology optimization method is required and given the ability of this method to generate optimum designs from an essentially 'blank canvas' warrants this development, especially for the design of special compliant mechanisms such as pressurized compliant structures [48][49][50].…”
Section: Ramifications On the Design Chainmentioning
confidence: 99%
“…This also includes pressure-actuated cellular structures (PACS, cf. Figure 1), which have so far only been investigated theoretically [1], [2]. The aim of this project is to develop theoretical and experimental basics for the development, production and testing of woven PACS.…”
Section: Introductionmentioning
confidence: 99%